Răspuns :
a x ( b + c + d ) = ab + ac + ad = 150 + 45 + 35 = 230
a x ( b - c + d ) = ab - ac + ad = 150 - 45 + 35 = 140
a x ( b - c - d ) = ab - ac - ad = 150 - 45 - 35 = 70
9a x ( b - c - d ) = 9ab - 9ac - 9ad = 9 x 150 - 9 x 45 - 9 x35 = 1350 - 405 - 315 = 630
a x ( b - c + d ) = ab - ac + ad = 150 - 45 + 35 = 140
a x ( b - c - d ) = ab - ac - ad = 150 - 45 - 35 = 70
9a x ( b - c - d ) = 9ab - 9ac - 9ad = 9 x 150 - 9 x 45 - 9 x35 = 1350 - 405 - 315 = 630
a)ax(b+c+d)= ab+ac+ad =150+45+35=195+35=230 b)ax(b-c+d)=ab-ac+ad=150-45+35=105+35=140 c)ax(b-c-d)=ab-ac-ad=150-45-35=105-35=70 d)9ax(b-c-d)=9ab-9ac-9ad=9x150-9x45-9x35=1350-405-315=945-315=630